Wonders and surprises: a collection of poems - McGinley, Phyllis, 1905-1976 (Philadelphia: Lippincott, 1968)
The author's selection of poems by contemporary English, Welsh, and American poets.
Keywords: American poetry. -- Collections; English poetry. -- Collections; American poetry; English poetry